Two implementations of 120 GHz transformer cross‐coupled oscillator based on cascode structure in 55 nm CMOS technology. Issue 12 (24th August 2022) - Yang, Shenghui
Abstract: Two oscillators are designed and fabricated, focusing on the output power and tuning range in the terahertz band. The first one is a transformer cross‐coupled oscillator based on the cascode structure, and the second one is a self‐mixing transformer cross‐coupled oscillator. Higher output power is obtained by using transformer coupling instead of direct or capacitive coupling. Using the frequency mixing principle, a wider tuning range is obtained. Both chips are processed by 55 nm CMOS technology. The measured frequency tuning range is 115.9–129.1 and 110.8–128.0 GHz, respectively. The measured peak value of output power is 3.2 and −14.3 dBm, respectively.